Optimization of understanding of the students 'mathematical concept through inquiry-based learning approach - Ernawati Ernawati; P I Lestari (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
The low understanding of students' concepts in learning mathematics is generally caused by several factors including the factors of lecturers using methods or learning approaches that are less relevant to teaching material resulting in a tendency to pump information to students, as a result they have not been able to improve understanding of concepts optimally, they cannot improve the competence of lecturers in learning activities, and also have not been able to develop student good behavior related to changes in understanding of concepts that need to be studied. This study uses a Classroom Action Research method through two cycles, applied to students in the mathematics education study program of FKIP UMMA academic 2018/2019 with a total of 30 student respondents. The results obtained by the inquiry-based learning approach can improve understanding of Mathematical concepts. In addition, inquiry-based learning approaches can improve teacher competencies in learning activities. After learning with the inquiry-based learning approach, it turns out that it can also develop students' good behavior related to changing understanding of Mathematical concepts. Generally, students who behave well and understand the concept of the majority, also increase the value of meeting the minimum completeness criteria = 65, always active, communicative, and passionate in learning with the quality of learning better than before